El retablo mayor de la iglesia parroquial de Sant Miquel de Castelltallat (d. 1613) y el triunfo de la Iglesia: lectura iconográfica y teológica - Galdeano Carretero, Rodolfo (Hispania sacra, 2024)
This study interprets that the set of images of the main altarpiece of the parish church of Sant Miquel de Castelltallat (Sant Mateu de Bages) preaches the next triumph of the Church; message ready to be proclaimed to the four winds from the watchtower of a peak, as is the case. The unusual scenes from the Old Testament, as well as the unprecedented representation of four angels framing the mystical embrace between Saint Francis and Saint Dominic, the reproduction of the legend of Mount Gargano in a sanctuary geography very close to the nearby mountain of Montserrat or the presentation of scenes from the Apocalypse announce a new golden age following the optimistic discourse of the medieval prophetic tradition and the renewed version of the eschatological and apocalyptic time of the conjuncture. In this sense, we interpret that the Apocalypse of the Jesuit Luis de Alcázar was a direct source for the iconological conception of the altarpiece.